Charge transfer induced by electronic state mixing in a symmetric X–Y–X-type multi-chromophore system. Issue 48 (11th December 2020) - Kim, Siin; Ahn, Doo-Sik; Ahn, Mina; Wee, Kyung-Ryang; Choi, Jungkweon; Ihee, Hyotcherl
Abstract : Py-Benz-Py exhibits unique photophysical properties attributable to the reduction of the energy gap between two electronic states by ESM, leading to ICT dynamics. Abstract : Charge transfer (CT) from electron donor (D) to acceptor (A) plays an important role in photoelectric or electrochemical devices and is a useful concept for a molecule with D and A well distinguishable. Here, we report our finding that even in a molecule with D and A not resolvable, CT can be induced by electronic state mixing (ESM) in a symmetric multi-chromophore system (MCS), namely 1, 4-di(1-pyrenyl)benzene (Py-Benz-Py). Unlike Py and Py-Benz, Py-Benz-Py exhibits unique photophysical properties attributable to the reduction of the energy gap between two electronic states induced by ESM. The ESM for Py-Benz-Py is due to the extended π-conjugation owing to the further introduction of Py into Py-Benz, and consequently leads to the favorable intramolecular CT, followed by the planarization due to the twisting motion between Py and phenyl moieties. Time-resolved spectroscopic data demonstrate that the twisting process of the Py moiety in acetonitrile occurs with two unequal time constants, suggesting the localized CT state and the asynchronous twisting dynamics of two Py moieties unlike the delocalized CT state in nonpolar and low-polarity solvents leading to the synchronous twisting of two Py moieties. This means that the symmetry-breaking CT in MCSs can induce an asynchronous twisting motion. The results reported here support that a molecule without CT can be turned into another molecule with CT induced by ESM and demonstrate that the excited-state relaxation dynamics can be regulated through the ESM induced by introducing the substituents or changing the environmental factors such as solvent polarities.